The landscape of PreK-12 engineering online resources for teachers - Kaloustian, Garene (2015)
Background The newly formed discipline of engineering education is addressing the need to (a) enhance STEM education for precollege students and (b) identify optimum ways to introduce engineering content starting, perhaps, from the early ages. Introducing engineering at the Prekindergarten through 12th grade (PreK-12) education level requires significant changes in teacher preparation and support. It highlights the need for developing developmentally appropriate content knowledge and pedagogical methods, thus revealing the challenges of preparing teachers to incorporate this type of knowledge base into their practice. Although professional development offered by universities, school districts, and other educational entities provides the primary source of formal learning tools for teachers, an increasing number of teachers also utilize other informal web-based resources regularly. This paper examines available PreK-12 engineering web resources offered by entities formally related to education in seven different languages, namely Arabic, Chinese (Mandarin), English, French, Greek, Korean, and Spanish. Results Findings showed how different educational systems designated different attention to the entry level ages when introducing engineering content. Differences in the terminology used to identify STEM resources for introducing these topics also became apparent. Similarities suggest that a large number of resources available on the web were originating in all researched languages. However, the developmental appropriateness and content validity of many of these resources remained questionable in many cases. In general, there was a plethora of isolated activities and lesson plans but significantly fewer complete engineering curricula available to teachers on the web. Conclusions This study presents a comparative analysis of the international landscape of PreK-12 engineering education and provides guidelines and samples of state-of-the art resources in each language for teachers interested in introducing their students to engineering as a reliable starting point towards PreK-12 engineering information gathering.